EFFECTIVENESS OF MUSICURE TO CONTROL PAIN IN BRONCHOSCOPY AT THE HOSPITAL DR. MOEWARDI SURAKARTA - Jayanti Revit; Wildan Ferdian; Debree Septiawan (Berkala Ilmiah Kedokteran Duta Wacana, 2023)
Background Sampling in bronchoscopy can lead to acute consequences, such as intrabronchial bleeding, bronchospasm, and pneumothorax. Bronchoscopies make patients uneasy because they fear discomfort and difficulty breathing. Hypnotherapy, music therapy, and aromatherapy can help during bronchoscopies. Musicure is considered to assist people to grow well by sending "passive" musical impulses.Objective The goal of this study was to see how well musicure helped bronchoscopy patients deal with pain.Methods A quasi-experimental design with a pre-test, post-test, and control group was used. Patients with lung illness will undergo bronchoscopy and consecutive sampling at the Dr. Moewardi Surakarta Hospital in February-March 2020. The study subjects were divided into a treatment group with Musicure and a control group without music. Both groups were assessed with pain visual acuity score (VAS)  at baseline and after bronchoscopy.Results A total of 32 subjects with lung diseases whom bronchoscopy in this study. The treatment group showed a decreased pain VAS scale (-14.71±12.31). The treatment group pre-test pain score obtained 31.76±12.86, and the VAS post-scale average of 17.06±12.63. The changes in the VAS scale post-pretreatment group showed a decrease in average -14.71±12.31. The treatment group (p=0.002) obtained a p<0.05, which means that the treatment group experienced a significant change in the VAS scale. There was a significant difference compared to the control (p<0.05).Conclusion Musicure is effective in inhibiting perception of pain that it will lower the VAS scale,  therefore decreasing pain score.  Pain in patients who undergo bronchoscopy will be more controlled, which makes it easier to act and decrease side effects after the action.